AN ANALYSIS OF GRAMMATICAL ERRORS IN THE WRITING OF PARAGRAPH BY THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Satria Bima Pratama Harwin; Fadly Azhar; Syarfi Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Research of the analysed grammatical errors was conducted in Mai 2019 in the Faculty of Teachers Training and Education University of Riau with the aim to analyz the students errors in writing some paragraph .The method used is the writing test. The objective of the study is to describe the grammatical errors and infer the causes or sources of those errors in writing made by the Fourth semester students of English FKIP UR The results show, the highest error category is the omission errors commited 281 times or 47.22% and the highest factor of errors is developmental committed errors 302 times or 35.99%Key Words: Writing, Error Analisys